Palynology of the permian Sanangoe-Mefidezi coal basin, Tete province, Mozambique and correlations with Gondwana microfloral assemblages - Mahabeer, Kierra Caprice (My University, 2017)
This study investigated the palynology of three boreholes (boreholes 12 ESD 231, 871L_D012 and 12 ESD 218) from the Sanangoe-Mefidezi Basin in the Tete Province, Mozambique in order to correlate the coal seams in Mozambique with other Gondwanan palynofloral assemblages. A total of 56 samples were prepared and examined with 27 of them being palynologically productive. All samples were prepared using the standard palynological preparation methods of Phipps and Playford (1984) and were examined and photographed under light microscopy. Palynomorph grains were generally fragmented due to transportation in high energy depositional environments, but identification to genus or species level was possible in most cases. A total of 41 taxa were identified which represented lycopods, sphenophytes, ferns, peltasperms, conifers and glossopterids. Statistical methods of clustering were applied as an unbiased method of subdividing palynomorph abundances through the three cores into zones and subzones. Four zones (the Scheuringipollenites ovatus-Deltoidospora directa Zone, the Scheuringipollenites ovatus-Alisporitespotoniei Zone, the Protohaploxypinus limpidus-Weylandites lucifer Zone and the Protohaploxypinus limpidus-Striatopodocarpites cancellatus Zone) and two sub-zones (the Punctatisporites gretensis Subzone and the Platysaccus papilionis Subzone) were established for the Sanangoe-Mefidezi Basin. Granulatasporites suhreticulatus and Plicatipollenites sp. were found to be restricted to the “Platform Facies”, whilst a number of taxa were present in two formations only. These restricted ranges can be utilised in future exploration work in the basin to determine which unit an unknown sample derives from. Correlations between the palynozones of the Sanangoe-Mefidezi Basin and assemblages from southern Africa, Antarctica and Australia were possible, suggesting an age range of Artinskian-Capitanian for the Vuzi, Moatize and Matinde formations. The thermal maturity index determined from palynomorph colour yielded a range of 4 to 5 on the Thermal Alteration Index of Batten (1980), indicating the potential for oil and wet gas production with transition into dry gas. This bodes well for future mining operations in the area. Palynological sampling of new cores in the Sanangoe-Mefidezi Basin would permit a more detailed record of the species present in these rocks, and would also determine whether the palynological event marking the base of the Matinde Formation can be laterally traced across the basin. Although reliable radioisotopic dates can be difficult to obtain, absolute ages for the Sanangoe-Mefidezi Basin rocks would be very useful in precisely calibrating the ages of the palynozones for future fossil fuel exploration as well as correlation with other Gondwanan palynoassemblages.
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Master of Science June, 2017